Indian Women in Social Service – With reference to Chudamani Raghavan’s “Herself” - PRIYA, N.S. VISHNU; V. N. SUDHEER (International Journal of Psychosocial Rehabilitation, 2020)
India is a country where women are worshipped as goddesses and many women have occupied the forfront in Indian politics. Hence, it is quite natural to think that all Indian women are empowered and are having an identity of their own. But the real scenario is entirely different. Many Indian women, though they are educated and are highly talented are not allowed to continue with their jobs or follow their passions in the name of family and children. Women who try to empower themselves are scorned at not only by men but also by women, that too their kinswomen. This situation of Indian women is beautifully pictured by Chudamani Raghavan in her short story “Herself”. The story depicts how an old woman after her late fifties and fulfilling all her responsibilities try to serve the society around her. This paper analyses the mind-set of the daughter who hates her mother doing social service and the determination of the old woman in following her passion.